THE CORRELATION BETWEEN POLYCYSTIC OVARY SYNDROME AND VITAMIN D DEFICIENCY: UNVEILING THE IMPACT OF LOW VITAMIN D LEVELS ON POLYCYSTIC OVARY SYNDROME SYMPTOMS - Dr Shweta Mendiratta; Dr Preeti Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Polycystic ovary syndrome (PCOS) is a prevalent hormonal disorder affecting 5-10% of women of reproductive age. Recent investigations highlight a potential link between PCOS and inflammation, with studies indicating elevated levels of inflammatory markers in women with PCOS compared to controls. This study involved 200 PCOS participants for investigation of impact of vitamin D with respect to clinical and metabolic traits and findings revealed that 60% of participants were vitamin D deficient (below 20 ng/mL). Deficiency was associated with higher rates of obesity (41.7% vs. 27.5%), oligo/amenorrhea (88.3% vs. 57.5%), and hirsutism (51.7% vs. 35%). Significant negative connections were observed between vitamin D levels and BMI, insulin resistance, androgen levels, hirsutism index, anovulatory cycles, and ovarian changes.